Optimal reliability and validity of measurement model in confirmatory factor analysis: different likert point scale experiment - Mohd Azry Abdul Malik (Tanjong Malim, 2021)
Optimal reliability and validity of measurement model in confirmatory factor analysis: different likert point scale experiment by Mohd Azry Abdul Malik